The Role of Financial Behavior, Financial Literacy, and Retirement Planning in Enhancing Lecturers' Financial Well-Being - Sunarmi Sunarmi; M. Yusuf S. Barusman; Andala R.P Barusman; Defrizal Defrizal; Yenny Marthalena (Yayasan Darussalam Bengkulu, 2026)
Background: Financial well-being among lecturers in private higher education institutions has become an important concern, particularly in developing countries where many lecturers receive relatively low salaries despite carrying substantial academic responsibilities. Financial well-being is essential not only for individual quality of life but also for maintaining productivity, job satisfaction, and institutional performance. However, empirical evidence regarding the determinants of financial well-being among private university lecturers remains limited. This study aims to examine the influence of financial literacy, financial behavior, retirement planning, and income on the financial well-being of lecturers in private higher education institutions. Methods: This study employed a quantitative research design using a cross-sectional survey approach. Data were collected from 310 lecturers working at private higher education institutions through an online questionnaire distributed via Google Forms. The measurement instruments were adapted from established scales in the financial well-being literature. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the measurement model and test the proposed structural relationships among variables. Results: The findings reveal that income is the strongest predictor of lecturers’ financial well-being (β = 0.543), followed by financial literacy (β = 0.442) and financial behavior (β = 0.264). The results indicate that lecturers with higher income levels, better financial knowledge, and healthier financial management practices tend to experience greater financial well-being. These findings highlight the importance of both economic resources and financial capability in shaping individual financial outcomes. Conclusion: The study concludes that improving lecturers’ financial well-being requires a multidimensional approach involving income enhancement, financial literacy development, and the promotion of positive financial behavior. Policymakers, higher education institutions, and relevant stakeholders should collaborate to provide financial education programs, retirement planning support, and policies aimed at improving lecturers’ economic conditions. Such initiatives can contribute to achieving sustainable financial well-being and improving the overall quality of academic life among private university lecturers.